2015
DOI: 10.3233/jpd-150540
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Subthalamic Stimulation can Improve Sleep Quality in Parkinson’s Disease

Abstract: Abstract.Background: Sleep problems are among the most common non-motor symptoms of Parkinson's disease (PD). The PD Sleep Scale 2nd version (PDSS-2) improved the original PDSS by adding more items on different aspects of sleep problems, making it a more robust tool to evaluate the severity of sleep disturbances. However, previous studies on deep brain stimulation (DBS) have not used the PDSS-2. Objective: To determine if the PDSS-2 could detect improvement reliably in sleep problems after bilateral subthalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…Deli and colleagues measured PDSS-2 scores in 13 participants with PD related sleep complaints before and after STN DBS and found significant improvement in quality of sleep at 1 year ( p < 0.001) (44). Hjort and colleagues assessed subjective sleep quality with PDSS questionnaire in 10 patients with bilateral STN DBS and compared results to controls who did not have DBS.…”
Section: Resultsmentioning
confidence: 99%
“…Deli and colleagues measured PDSS-2 scores in 13 participants with PD related sleep complaints before and after STN DBS and found significant improvement in quality of sleep at 1 year ( p < 0.001) (44). Hjort and colleagues assessed subjective sleep quality with PDSS questionnaire in 10 patients with bilateral STN DBS and compared results to controls who did not have DBS.…”
Section: Resultsmentioning
confidence: 99%
“…First, PDSS-2 was utilized in a doubleblind, placebo-controlled trial assessing the efficacy of rotigotine on nocturnal disabilities 7 . Recently the responsiveness of PDSS-2 was also demonstrated after various therapeutic interventions including levodopa/carbidopa intestinal gel 8 infusion and bilateral subthalamic deep brain stimulation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Although in 12 patients, Chou and coworkers demonstrated statistically nonsignificant improvement in parts 1 and 2 (1.3 and 3.6 points, respectively) [29], in another study, this group revealed 3.1- and 5.3-point improvement ( p < 0.05, n = 27 patients) [28]. Aiming to evaluate sleep-quality, Deli et al [30 ]showed 4.2- and 7.4-point improvement 1 year after DBS implantation ( p < 0.01, n = 25). Jafari et al [31 ]reported 4.26 points ( n = 30, p < 0.001) on part 1 and 8.5 points on part 2 ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only a few studies used the MDS-UPDRS to reveal the changes associated with STN DBS. We identified 5 studies using the keywords “MDS-UPDRS” and “DBS” or “deep brain stimulation” on July 30, 2016 [28,29,30,31,32]. Although in 12 patients, Chou and coworkers demonstrated statistically nonsignificant improvement in parts 1 and 2 (1.3 and 3.6 points, respectively) [29], in another study, this group revealed 3.1- and 5.3-point improvement ( p < 0.05, n = 27 patients) [28].…”
Section: Discussionmentioning
confidence: 99%